Disconjugacy characterization by means of spectral (k, n−k) problems. (February 2016) - Cabada, Alberto; Saavedra, Lorena
Abstract: This paper is devoted to the description of the interval of parameters for which the, parameter dependence, general linear n th-order ordinary differential equation is disconjugate on a given bounded interval I . Such interval is characterized by the closest to zero eigenvalues of the considered problem coupled with the so-called ( k, n − k ) boundary conditions.